1996
DOI: 10.1073/pnas.93.5.2180
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the C terminus of the amyloid precursor protein alters growth factor responsiveness in stably transfected PC12 cells.

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…To examine the Rab5 + endosomes in axons, we expressed C99 and C83 following NGF treatment. Consistent with earlier studies (73)(74)(75), expression of C99 markedly suppressed NGF-induced activation of Erk1/2 at both 5 and 30 minutes (Supplemental Figure 2, B and C). While having no effect at 5 minutes, C83 induced a small decrease in pErk1/2 at 30 minutes.…”
Section: M596vsupporting
confidence: 79%
“…To examine the Rab5 + endosomes in axons, we expressed C99 and C83 following NGF treatment. Consistent with earlier studies (73)(74)(75), expression of C99 markedly suppressed NGF-induced activation of Erk1/2 at both 5 and 30 minutes (Supplemental Figure 2, B and C). While having no effect at 5 minutes, C83 induced a small decrease in pErk1/2 at 30 minutes.…”
Section: M596vsupporting
confidence: 79%
“…Thus, primary hippocampal neurons may be more vulnerable to the stresses resulting from overexpression of h-APP than are the PC12 cells. As discussed above, elevated intracellular levels of the full-length APP in the infected cells may lead to more CTF and/or A␤ protein production, which may have toxic effects on the cultured cells (Koh et al, 1990;Cotman et al, 1992;Malouf, 1992;Busciglio et al, 1993;Jarrett et al, 1993;Shearman et al, 1994;Simmons et al, 1994;Kaneko et al, 1995;Harris et al, 1996;Itoh et al, 1996;Sandhu et al, 1996;Blanc et al, 1997;Mark et al, 1997;Lambert et al, 1998). Nishimura et al (1998) reported that injection of adenovirus overexpressing wt human APP in rat hippocampus caused neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This antibody precipitates total A␤ and p3 (and small variable amounts of APP s ) from the medium of cultured cells (18). Polyclonal antibody 1963 was raised to synthetic A␤ [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] (18). The monoclonal antibody 2G3, specific for A␤ x-40, was produced by injecting female A͞J mice intraperitoneally with…”
Section: Pulse-chase Experiments and Immunoprecipitationsmentioning
confidence: 99%